Hubungan Perilaku (PHBS) Anak Dengan Kejadian Kecacingan DI SDN 2 Sukamenanti Kota Bandar Lampung - Haryatmi, Dwi (Universitas Muhammadiyah Semarang, 2024)
Background: Personal hygiene is one of the behaviors that must be applied in everyday life. Children are an age group that is very low in implementing personal hygiene. Children who do not adopt clean and healthy living habits are very susceptible to helminthiasis.The occurrence of worms in children can occur because of the possibility of worm eggs in the environment that stick to the hands and then being swallowed.The worm eggs then multiply in the host's body which causes the host to experience several symptoms such as dizziness, weakness, lethargy, loss of appetite, lack of blood and even nausea and vomiting.This study aims to determine whether there is a relationship between personal hygiene in children which includes washing hands before eating, cutting nails once a week, wearing footwear when playing in the environment and washing hands with soap after defecating with helminthiasis. The inspection method uses the direct method with an analytic design using a cross sectional approach. The statistical test uses the chi square test to determine the relationship between clean and healthy living behavior and the incidence of helminthiasis. From the examination results, it was found that 41 (26.11%) students at SDN 2 Sukamenanti in Bandar Lampung City experienced positive helminthiasis and 116 (73.89%) students were negative for helminthiasis and a significant relationship was found between clean and healthy living behavior (PHBS) and helminthiasis (pValue = 0.000) and there were 41 (26.11%) students who had helminthiasis and 13 (8.28%) students had bad clean and healthy living behavior